Monitoring UV‐induced signalling pathways in an ex vivo skin organ culture model using phospho‐antibody array. Issue 5 (21st February 2018) - Lenain, Christelle; Gamboa, Bastien; Perrin, Agnes; Séraïdaris, Alexia; Bertino, Béatrice; Rival, Yves; Bernardi, Mathieu; Piwnica, David; Méhul, Bruno
Abstract: We investigated UV‐induced signalling in an ex vivo skin organ culture model using phospho‐antibody array. Phosphorylation modulations were analysed in time‐course experiments following exposure to solar‐simulated UV and validated by Western blot analyses. We found that UV induced P‐p38 and its substrates, P‐ERK1/2 and P‐AKT, which were previously shown to be upregulated by UV in cultured keratinocytes and in vivo human skin. This indicates that phospho‐antibody array applied to ex vivo skin organ culture is a relevant experimental system to investigate signalling events following perturbations. As the identified proteins are components of pathways implicated in skin tumorigenesis, UV‐exposed skin organ culture model could be used to investigate the effect on these pathways of NMSC cancer drug candidates. In addition, we found that phospho‐HCK is induced upon UV exposure, producing a new candidate for future studies investigating its role in the skin response to UV and UV‐induced carcinogenesis.